Somewhere safe with somebody good [compact disc, unabridged] - Karon, Jan, 1937- (Karon, Jan, 1937- Mitford years, 2014)
After five hectic years of retirement from Lord's Chapel, Father Tim Kavanagh returns with his wife, Cynthia, from a so-called pleasure trip to the land of his Irish ancestors. While glad to be at home in Mitford, something is definitely missing: a pulpit. But when he's offered one, he decides he doesn't want it. Maybe he's lost his passion.